Akses Pelayanan Kesehatan Mental di Negara Berkembang - Mardatillah (Yayasan Darussalam Bengkulu, 2024)
According to the World Health Organization (WHO), mental health is a state of wellbeing that a person is aware of that includes the ability to manage life's stresses in a sensible way, to work productively and fruitfully, and to participate in their community.The importance of learning about mental health services is that mental health does not only mean the absence of mental disorders, but also includes a person's ability to cope with stress, develop personally, and build healthy relationships. By getting good mental health services, a person can get professional support to manage emotional problems, prevent more serious psychological disorders, improve their quality of life. The research method uses a literature study, by analyzing 21 journals as primary data. Data analysis with several stages, the first stage determines the theme, the second stage selects journal articles that are relevant to the theme and in accordance with the last 6 years, the third stage of the review process as many as 7 journal articles, the fourth stage of categorization and the fifth stage of drawing conclusions. Research results